2006
DOI: 10.1128/iai.00376-06
|View full text |Cite
|
Sign up to set email alerts
|

Uropathogenic Escherichia coli Induces Extrinsic and Intrinsic Cascades To Initiate Urothelial Apoptosis

Abstract: A murine model of urinary tract infection identified urothelial apoptosis as a key event in the pathogenesis mediated by uropathogenic Escherichia coli (UPEC), yet the mechanism of this important host response is not well characterized. We employed a culture model of UPEC-urothelium interactions to examine the biochemical events associated with urothelial apoptosis induced by the UPEC strain NU14. NU14 induced DNA cleavage within 5 h that was inhibited by the broad caspase inhibitor ZVAD, and urothelial caspas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 39 publications
2
73
0
Order By: Relevance
“…For example, the HlyA-positive UPEC isolate CP9 was recently shown to induce rapid activation of proapoptotic executioner caspases in neutrophils much more efficiently than a HlyA-negative mutant (Russo et al, 2005). Relative to an isogenic hlyA mutant, the wild-type CP9 strain also induces more robust exfoliation of bladder epithelial cells (Smith et al, 2006), a phenomenon that seems to involve activation of apoptotic pathways (Mulvey et al, 1998;Schaeffer et al, 2004;Klumpp et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, the HlyA-positive UPEC isolate CP9 was recently shown to induce rapid activation of proapoptotic executioner caspases in neutrophils much more efficiently than a HlyA-negative mutant (Russo et al, 2005). Relative to an isogenic hlyA mutant, the wild-type CP9 strain also induces more robust exfoliation of bladder epithelial cells (Smith et al, 2006), a phenomenon that seems to involve activation of apoptotic pathways (Mulvey et al, 1998;Schaeffer et al, 2004;Klumpp et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been suggested that the FimH adhesin localized at the tips of type 1 pili can function as a tethered toxin (Klumpp et al, 2006), raising the possibility that FimH functions synergistically with HlyA in promoting Akt dephosphorylation. However, we found that a UTI89 ⌬fimH mutant is able to inactivate Akt like the wild-type isolate, indicating that HlyA-mediated dephosphorylation of Akt does not require functional type 1 pili ( Figure 2E).…”
Section: Hlya Stimulates Akt Dephosphorylationmentioning
confidence: 99%
See 2 more Smart Citations
“…Lectin-like type 1 fimbriae are also responsible for the mannose-sensitive (binding) adhesion to host (mammalian) cells (Schilling et al, 2001;Duncan et al, 2005). Such microbe-host protein-carbohydrate interaction (Karlsson, 2001) is not only the essential step to produce infection, but also it leads to a status alternation of the host cells, for instance, the induction of apoptosis (Mulvey et al, 1998;Klumpp et al, 2006). Engineered bacteria are able to help control cancer (Jain and Forbes, 2001).…”
Section: Introductionmentioning
confidence: 99%